Ergonomic design of school furniture: challenges for the portuguese schools - Castellucci, Ignacio (2010)
It can be observed an increased concern about the school classrooms, in particular about the study and design of school furniture fitting the students’ needs and anthropometrics characteristics. The main aim of this study was to perform an anthropometric survey, considering the main anthropometric dimensions and, in accordance, to define the dimensions and characteristics of school furniture for Portuguese students of the 1st education cycle using valuable and validated ergonomic criteria. The analyzed sample includes, so far, 432 students. Obtained results seem to reinforce the need to consider the specificity of the anthropometric characteristics of the Portuguese students by adding an extra size mark for school furniture in a future revision of the corresponding standard.